Efektivitas Penggunaan Cooperative Learning Tipe Two Stay – Two Stray (TS – TS) Berbantuan Platform Pembelajaran Kahoot! Pada Mata Pelajaran Ekonomi Terhadap Peningkatan Berpikir Kreatif Siswa - Rahayu, Mila Siti; Srigustini, Astri; Widyaningrum, Bakti (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research is motivated by the problems that occur in SMA Negeri 9 Tasikmalaya, namely the low ability of students' creative thinking in economic subjects. The purpose of this study was to determine the effectiveness of using cooperative learning type Two Stay - Two Stray (TS-TS) assisted by kahoot learning platform in economic subjects on improving students' creative thinking. The method used in this research is quasi experiment with nonequivalent control group design, and data collection techniques through tests in the form of essay questions. The population in this study was class XI IPS at SMA Negeri 9 Tasikmalaya which amounted to 180. The sample used was class XI IPS B3 which amounted to 36 people as an experimental class and class XI IPS C2 which amounted to 34 people as a control class with sampling using purposive sampling. Data analysis techniques using SPSS 23 software assistance, namely paired samples T-Test and independent Samples T-Test tests with a significance level of 5% or 0.05. Based on the results of the study obtained a Sig. (2-Tailed) value of 0.000 <0.05 which indicates that H0 is rejected and Ha is accepted, so it can be seen that there is an effectiveness of using the cooperative learning model type two stay-two stray (TS-TS) assisted by the Kahoot learning platform on increasing students' creative thinking in economic subjects.